2020
DOI: 10.32672/jse.v5i3.2145
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Koagulan Biji Asam Jawa (Tamarindus indica) Terhadap Efisiensi Penurunan Zat Organik Pada Air Gambut

Abstract: Organic substances in peat water cause smell, have a brown color and taste, in addition to that it can interfere the processing process by forming carcinogenic trihalomethane which is produced from the reaction between organic compounds and chlorine. Peat water used in this study came from the village of Tuah Indrapura, Siak Regency with a concentration of organic matter of 95.2 mg/L. Based on Permenkes No. 492 of 2010 the concentration of organic substances exceeds the quality standard, so it needs to be trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(5 reference statements)
0
1
0
1
Order By: Relevance
“…Based on interviews with two students about the ease of understanding and the ability to stimulate interest in learning, the results showed that students were interested in this practicum design because it was easy and could increase their understanding of the nature of colloidal coagulation. Using appropriate media for the material being taught effectively stimulates student interest, increases participation in the teaching and learning process, and enables students to easily grasp the material, thus increasing student achievement (Rasanzani et al, 2017).…”
Section: The Feasibility Of a Water Purification Practicum Using Tama...mentioning
confidence: 99%
“…Based on interviews with two students about the ease of understanding and the ability to stimulate interest in learning, the results showed that students were interested in this practicum design because it was easy and could increase their understanding of the nature of colloidal coagulation. Using appropriate media for the material being taught effectively stimulates student interest, increases participation in the teaching and learning process, and enables students to easily grasp the material, thus increasing student achievement (Rasanzani et al, 2017).…”
Section: The Feasibility Of a Water Purification Practicum Using Tama...mentioning
confidence: 99%
“…Biji asam jawa mengandung tannin dan beragam senyawa polifenol seperti katekin, serta banyak jenis procyanidin. Khususnya, oligomer procyanidin tetramer sekitar 30,2%, procyanidin heksamer sebesar 23,8%, procyanidin trimer sekitar 18,1%, procyanidin pentamer sebesar 17,6%, procyanidin B2 sekitar 5,5%, epikatekin sebesar 4,8%, dan juga taxifolin, apigenin, eriodictyol, luteolin, dan naringenin (Riyandini & Iqbal, 2020). Tanin berfungsi sebagai adstringen yang memiliki kemampuan untuk menyusutkan selaput lendir usus, sehingga seringkali digunakan sebagai pengobatan antidiare (Rahmadani, 2021).…”
unclassified